Thromboelastrography (TEG) Is Still Relevant in the 21st Century as a Point-of-Care Test for Monitoring Coagulation Status in the Cardiac Surgical Suite. (September 2017) - Hernandez Conte, Antonio; Perotti, Deena; Farac, Lauren
Since their introduction into clinical practice in the early 1960s, viscoelastic point-of-care (POC) testing—thromboelastrography (TEG) and thromboelastrometry (ROTEM)—has become increasingly popular in intensive care units, operating rooms, and emergency room settings. As TEG has been an established POC viscoelastic testing modality for many years, there has been more research and analysis of its utility and ability to reduce transfusions in the general, cardiac, and liver surgical sectors compared with ROTEM. The role of TEG versus ROTEM has been greatly disputed, although both continue to be utilized in the cardiac suite to guide transfusion in cardiac surgery as these procedures produce a profoundly different form of bleeding compared to other surgical interventions.